PROGRAM SIMARAK: KOLABORASI SEKOLAH DAN KELUARGA DALAM PENGUATAN LITERASI - Mita Hidayanti; Vina Nur Indah Sari (LPMP Provinsi DKI Jakarta, 2026)
This study aims to describe the implementation of the SIMARAK (Students Reading with Family) program as a form of collaboration between schools and families in strengthening literacy among elementary school students. The study employed a descriptive qualitative approach with data collected through open-ended questionnaires distributed to teachers, parents, and students involved in the SIMARAK program. The data were analyzed through data reduction, data display, and conclusion drawing to identify patterns of program implementation, forms of family involvement in shared reading activities, and their impact on students’ reading habits. The findings indicate that the SIMARAK program extends literacy practices from the school environment to the home through shared reading activities involving parents directly. Family participation in reading activities provides opportunities for students to interact more intensively with texts, fosters reading interest, and increases students’ engagement in literacy activities. Literacy interactions between parents and children during shared reading also contribute to improving reading comprehension and developing students’ reading habits. The findings suggest that the SIMARAK program can serve as a strategy for strengthening students’ literacy through family literacy practices integrated with school literacy programs. Therefore, collaboration between schools and families through shared reading activities has the potential to support the development of a sustainable literacy culture among elementary school students.